Modeling the Grain Import Trade: A Cointegration Analysis of China’s Panel Data - Feng Zhao; Pingping Sun; Jie Zhang (Discrete Dynamics in Nature and Society)
In recent years, China has become the world’s largest importer of grain, and scholars have particularly examined whether China’s grain import trade presents this effect. By applying cointegration analysis to trade statistics panel data of China’s wheat, corn, rice, and soybean production and imports from January 2016 to December 2019, this paper empirically tests for the existence of the great country effect in China’s grain import trade. The results show that during the sample period, there is a long-term stable equilibrium relationship between the import volume, domestic price, and international price of the four major grains; the great country effect in the import trade of wheat and rice is not significant. The imports of corn and soybean present a great country effect to a certain extent in the short term; moreover, a change in the grain price in the international market does not lead to a change in China’s grain import volume, which shows that the great country effect in China’s grain import trade is distorted. Therefore, China should pay close attention to the impact of international factors on the fluctuation of its own food prices and enhance its ability to rationally utilize the international food market and international agricultural resources to ensure domestic food security.